1997
DOI: 10.1136/vr.141.15.383
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of ivermectin and moxidectin in the control of naturally acquired cyathostome infections in horses

Abstract: The control of naturally acquired cyathostome infections in horses by treatments with ivermectin and moxidectin was evaluated in three field studies. In a first study the efficacy of both drugs was assessed in a faecal egg count reduction test. Both ivermectin and moxidectin demonstrated efficacies greater than 99 per cent for up to 60 days after treatment. In a second study, the period required for strongyle eggs to reappear was estimated in horses treated either with ivermectin or moxidectin. For the horses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 19 publications
5
27
0
Order By: Relevance
“…Nematodes were excreted in the periods similar to those observed by other authors (Demeulenaere et al 1997, Abbot et al 2003, Osterman Lind et al 2003, Steinbach et al 2006. No significant differences were observed in the egg reappearance period (ERP) which was estimated at 9-10 weeks in both seasons, and the above is even longer compared with the findings of other authors (Bello 1996, Demeulenaere et al 1997, Reinemeyer and Clymer 2002. Demeulenaere et al (1997) suggested that the egg reappearance period should be redefined as "the period after antihelmintic treatment during which no eggs or small but acceptable numbers of eggs are excreted".…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Nematodes were excreted in the periods similar to those observed by other authors (Demeulenaere et al 1997, Abbot et al 2003, Osterman Lind et al 2003, Steinbach et al 2006. No significant differences were observed in the egg reappearance period (ERP) which was estimated at 9-10 weeks in both seasons, and the above is even longer compared with the findings of other authors (Bello 1996, Demeulenaere et al 1997, Reinemeyer and Clymer 2002. Demeulenaere et al (1997) suggested that the egg reappearance period should be redefined as "the period after antihelmintic treatment during which no eggs or small but acceptable numbers of eggs are excreted".…”
Section: Discussionsupporting
confidence: 76%
“…Despite differences in serum drug concentrations between spring and autumn treatments, a comparable clinical effect was achieved. Nematodes were excreted in the periods similar to those observed by other authors (Demeulenaere et al 1997, Abbot et al 2003, Osterman Lind et al 2003, Steinbach et al 2006. No significant differences were observed in the egg reappearance period (ERP) which was estimated at 9-10 weeks in both seasons, and the above is even longer compared with the findings of other authors (Bello 1996, Demeulenaere et al 1997, Reinemeyer and Clymer 2002.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…According to published data (2,4,18), the egg reappearance period (ERP) after ivermectin treatment lasts from 8 to 12 weeks. The results of our study corroborate the above findings.…”
Section: Discussionmentioning
confidence: 99%